Digital surface, terrain, and canopy height models for Deception Creek Experimental Forest in 2011 - Benjamin C. Bright (19657240) (2025)
This data publication contains three digital rasters with a spatial resolution of one meter: 1) a digital surface model (DSM), which represents the highest lidar return in each grid cell; 2) a digital terrain model (DTM), a representation of the ground surface with vegetation and other non-ground returns removed; and 3) a canopy height model (CHM), a representation of the height of vegetation above the ground surface. Digital rasters were derived from lidar data that were acquired over Deception Creek Experimental Forest, Idaho, USA in 2011. To provide a high-resolution representation of vegetation structure across Deception Creek Experimental Forest.